ANALISIS VEGETASI GULMA PADA PERKEBUNAN KELAPA SAWIT (Elaeis quinensis Jacq.) di DESA SUKA MAJU KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Afrianti, Iis; Yolanda, Rofiza; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this study was to determine composition and structure of weeds in oil palm plantations (Elaeis quinensis Jacq.) in Suka Maju Village Rambah subdistrict Rokan Hulu Regency. The study was conducted from September to December 2014 by using survey method with purposive sampling technique at each station with different age:3-5 years, 5-7 years, and >7 yearsand 3 repetitions. Results showed 17 families and 40 species of weeds were found. Density value ranges 0.01-14.15; KR: 1.1-70.38; Frequency: 0.08-1.00; FR: 0.59%- 7,10%; NP: 0.59%-76.89%; Hâ: 2.16-2.58 C: 0.12-0.20; J: 0.65-0.78 and similarity index 66.6%- 75.8%.